Improved Mobilome Delineation in Fragmented Genomes - Mageeney, Catherine M.; Trubl, Gareth; Williams, Kelly P. (Frontiers in Bioinformatics, 2022)
The mobilome of a microbe, i.e., its set of mobile elements, has major effects on its ecology, and is important to delineate properly in each genome. This becomes more challenging for incomplete genomes, and even more so for metagenome-assembled genomes (MAGs), where misbinning of scaffolds and other losses can occur. Genomic islands (GIs), which integrate into the host chromosome, are a major component of the mobilome. Our GI-detection software TIGER, unique in its precise mapping of GI termini, was applied to 74 561 genomes from 2473 microbial species, each species containing at least one MAG and one isolate genome. A species-normalized deficit of ~1.6 GIs/genome was measured for MAGs relative to isolates. To test whether this undercount was due to the higher fragmentation of MAG genomes, we updated TIGER to enable detection of split GIs whose termini are on separate scaffolds or that wrap around the origin of a circular replicon. The GI yield doubled with SplitTIGER, and the new split GIs matched the quality of single-scaffold GIs, except that highly fragmented GIs may lack central portions. Cross-scaffold search is an important upgrade to GI detection as fragmented genomes increasingly dominate public databases. SplitTIGER better captures MAG microdiversity, recovering niche-defining GIs and supporting microbiome research aims such as virus-host linking and ecological assessment.